Peran Guru Bimbingan dan Konseling dalam Mengatasi Siswa dengan Tipe Kepribadian Introvert di SMPN I Pragaan, Kecamatan Pragaan Kabupaten Sumenep - Karim Abubakar (Journal of Public Policy Analys, 2025)
The role of the guidance and counseling teacher is as an educator, mentor, and also as a motivator for students. Teachers have a role in guidance and counseling to direct and develop the capacity of students. The problem studied in this study is the role of guidance and counseling teachers in dealing with students with introverted personality types. The researcher was interested in this research and the focus of the research was how introvert personality types are at SMPN I Pragaan, Pragaan District, Sumenep Regency and what is the role of guidance and counseling teachers in dealing with students with introverted personalities at SMPN I Pragaan, Pragaan District, Sumenep Regency. The type of research used is a qualitative approach with a descriptive type and three data analysis methods are used, namely data reduction, data presentation, and drawing conclusions. The results of the research and discussion can be concluded that the role of guidance and counseling teachers in overcoming students with introverted personality types at SMPN I Pragaan, Pragaan District, Sumenep Regency includes: the role of the guidance and counseling teacher acts as a guide, educates, and as a motivator for introverted students. As for the role of the guidance and counseling teacher in overcoming introverted student personality factors such as family, friend, self, and task factors. While the services provided by guidance and counseling teachers to introverted students such as individual or group services, building interactions,public speaking, and provide opportunities for students to make their own decisions without any coercion from others.